2015
DOI: 10.1161/circresaha.115.306850
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Intracoronary Allogeneic Mesenchymal Stem Cells and Cardiosphere-Derived Cells in Swine with Hibernating Myocardium

Abstract: Rationale Allogeneic bone marrow-derived mesenchymal stem cells (MSCs) and cardiosphere-derived cells (CDCs) have each entered clinical trials but a direct comparison of these cell types has not been performed in a large animal model of hibernating myocardium. Objective Using completely blinded methodology, compare the efficacy of global intracoronary allogeneic MSCs (icMSCs, ~35×106) and CDCs (icCDCs, ~35×106) vs. vehicle in cyclosporine-immunosuppressed swine with a chronic LAD stenosis (n=26). Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 49 publications
1
56
1
Order By: Relevance
“…Nevertheless, endothelial cells cocultured with control Scr CDCs showed increased migration and tube formation in an in vitro angiogenesis assay which was blocked by inhibiting exosome release with knockdown of nSMase2. This stimulation of angiogenic activity is consistent with our previous in vivo results showing increased capillary density throughout the heart following intracoronary injection of CDCs in swine with hibernating myocardium[1, 2]. It is also consistent with the increase in capillary density found after focal injection of purified CDC derived exosomes into the border zone of a murine infarction by others [15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, endothelial cells cocultured with control Scr CDCs showed increased migration and tube formation in an in vitro angiogenesis assay which was blocked by inhibiting exosome release with knockdown of nSMase2. This stimulation of angiogenic activity is consistent with our previous in vivo results showing increased capillary density throughout the heart following intracoronary injection of CDCs in swine with hibernating myocardium[1, 2]. It is also consistent with the increase in capillary density found after focal injection of purified CDC derived exosomes into the border zone of a murine infarction by others [15].…”
Section: Discussionsupporting
confidence: 92%
“…This passage also corresponds to the passage of CDCs transplanted into our porcine model of hibernating myocardium [1, 2]. As a control, we also isolated exosomes from normal human dermal fibroblasts (NHDF) at P4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, genetic lineage-fate mapping studies show that, under the proper conditions, endogenous CPCs (145,348,368), and to a smaller extent BMCs (289,396) and MSCs (60,144,290) produce new cardiomyocytes in the postnatal heart, albeit at a functionally insignificant level. Paradoxically, compared with ESC/iPSC-based strategies, engraftment of MSCs and CPCs is lower but leads to significant heart regeneration and recovery of heart function (62,97,119,137,143,144,147,174,175,228,229,284,290,321,322,385). Ex vivo tissue engineering approaches, whereby MSCs are combined or fused with adult human CPCs (175, 291,392), ESC/iPSC-derived CPCs (42), endothelial progenitors (417), and possibly neurons (224,389) may improve long-term engraftment and/or differentiation of the adult cell grafts and therefore lead to a meaningful level of myocardial regeneration and functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…While this requires transient aortic occlusion and is technically challenging in the rodent heart, it is straightforward to accomplish in humans and large animals by direct intracoronary infusion. Suzuki demonstrated that continuous intracoronary infusion was efficacious without cessation of coronary flow and stimulated myocyte proliferation throughout the diseased but not normal heart after widespread intracoronary MSC and CDC administration to swine with hibernating myocardium 10, 11, 13 . Others have shown that transient occlusion or “stop flow” is not required for CSC or CDC uptake and demonstrated functional efficacy of CDCs administered without cessation of flow following acute myocardial infarction 14, 15 .…”
mentioning
confidence: 99%